Atmosphere Control of a House - Madaleno, I.; Branco, S. (Open Schools Journal for Open Science, 2020)
The project consists of the prototype of a house, whose atmosphere is controlled automatically. Specific Aims of learning: studying the Arduíno board and sensors for collecting information, controlling and executing actions, knowing the language of programming needed, searching for solutions to the challenges using technological resources. With this project, the students got to know better the functioning of some sensors and how to apply them in other contexts. And they realized the importance of home automation in people's lives.